A conectividade possibilita o aumento da pressão de propágulos de Limnoperna fortunei (Dunker, 1857). - Amo, Vanessa Ernandes de (2018)
The spread of organisms in floodplains is favored by connectivity between habitats. In this way, it is possible that invasive species have an increased propagules pressure in these ecosystems. Here, we tested the hypothesis that the connection between habitat raises the larval density of Limnoperna fortunei. In order to test the hypothesis, we performed samplings in connected and isolated shallow floodplain lakes in the upper Paraná River, filtering lake water through a plankton net to evaluate the density of L. fortunei larvae. Abiotic variables were also sampled to evaluate physical and chemical differences of water between the sampled environments, but did not present significant difference. However, total density of larvae and density of each larval stages differed between lake, except for the Pedivéliger stage. Larger densities were recorded in the lakes connected to the main river of the floodplain, where the occurrence of larvae of L. fortunei is massive. The results corroborate the hypothesis that the connection between habitat raises the density of larvae, suggesting that environments connected to sources of invasive propagules suffer greater propagule pressure. Thus, the connectivity between habitat is a relevant factor to be considered in actions of control and management of this species.